Implementation of User-Centered Design (UCD) in Developing a Mobile Attendance Application to Improve User Experience - Ria Andriani (SCOPUS ID: 57208011426); Ade Pujianto; Abdullah Abdullah (SISTEMASI, 2026)
The desktop- or web-based attendance system currently used by Sevenpion is considered to have suboptimal performance, particularly in terms of speed and user convenience. This limitation is primarily due to the system’s reliance on web browsers, internet connection stability, and a user interface that is not fully responsive on mobile devices. This study aims to design a more comfortable, efficient, and adaptive mobile attendance application by improving its user interface (UI) and user experience (UX). The design process follows a User-Centered Design (UCD) approach, which emphasizes user needs through stages including requirements identification, context-of-use analysis, prototyping from low- to high-fidelity, and system evaluation. Usability testing was conducted using the System Usability Scale (SUS) method, involving five participants, yielding an average score of 77, categorized as “Good.” The results indicate that the prototype application enhances comfort, security, and efficiency in the attendance process compared to the existing web-based system. The study highlights the importance of user-centered approaches in mobile application development to ensure optimal usability.